The role of information technology systems (IT) on the development of effective internal controls. desktop study - Wadesango, Newman; Yolanda, Sandu; Sitsha, Lovemore (Economic and Social Development (JESD), 2024)
Research Question: What is the role of Information Technology on the development of effective internal controls of companies? Motivation: Companies can now support operations with IT systems to improve operating performance. As a result, companies must adapt their technique and method of internal control in accordance with computerization (AIS) to exercise effective control because the adaptation of quality internal control has an impact on operations and the achievement of operations Idea: The purpose of the study was to establish the role of Information Technology Systems (IT) on the development of effective internal controls. Data: A literature review methodology drawing on grey literature and published work elicited data for the study Tools: it can be denoted that despite the importance of information systems, challenges are imminent when adopting and implementing them. Staff should have the ability to embrace the system as well as finding the best system to use Findings: The findings indicated that information systems pose challenges when trying to adopt them. The major challenge was finding the best compatible information system and having the staff that portray familiarity and knowledge of the information systems. Contribution: Companies should support operations with IT systems to improve operating performance. As a result, companies must adapt their technique and method of internal control in accordance with computerization (AIS) to exercise effective control because the adaptation of quality internal control has an impact on operations and the achievement of operations.
Journal of Economic and Social Development (JESD) – Resilient Society Vol. 11, No.2, September 2024
Keywords: Information Technology Systems; Internal Controls; Information technology; Business